Radical-driven degradation mechanism of Cu(II)-EDTA during supercritical water gasification: Insights from ReaxFF molecular dynamics - Tingting Dai; Xiaoxia Guo; Ruochen Xiong; Weiqiang Liu; Weilong Yin; Weichong Deng; Wenwen Wei; Shi Liu; Wen Cao (Journal of Environmental Chemical Engineering, 2026)

An all-in-one endoluminal acoustofluidic system enables spatiotemporal transmucosal drug delivery and barrier repair for inflammatory bowel disease - Yichen Liu; Xiaoming Zheng; Yang Qin; Jing Han; Zhiwei Cong; Shu Fan; Yan Li; Ruochen Wang; Xiaolong Guo; Qichao Huang; Xunan Jing; Yibo Liu; et al. (Chemical Engineering Journal, 2026)

A Novel LEC Framework Incorporating Source Resolution: Spatiotemporal Evolution and Multi-Scenario Prediction of Soil Heavy Metal Risks - Xiufang Zhao; Kang Hou; Yujie Zhu; Xiaoping Li; Zeyu Liu; Xinyuan Zhu; Ruochen Mei; Luohong Zhang; Xuxiang Li (Journal of Environmental Chemical Engineering, 2026)

A multi-model fusion framework for assessing microscale carbon stock dynamics and ecological quality regulation - Ruoxi Li; Kang Hou; Yuxiang Xue; Bo Zhang; Ruochen Mei; Zhao Liu; Xuxiang Li (Environment, Development and Sustainability, 2026)

Multidimensional urbanization and agricultural carbon emission intensity in belt and road countries: A spatial quantile regression analysis - Xuan Liu; Liuyang Yao; Yu Lai; Ruochen Tian; Ziqing Tian; MinJuan Zhao (Environment, Development and Sustainability, 2026)

Sustainable vertical barriers using solidified marine mud: Hydraulic and mechanical behavior of lithium slag-fly ash geopolymer composites - Zhongxing Ping; Haoqing Xu; Songyu Liu; Yong Yue; Ruochen Wang; Nan Zhang (Process Safety and Environmental Protection, 2026)

Multi-objective optimization of rice production and environmental sustainability under climate change in the Yangtze River Delta: A DNDC-random forest framework approach - Shuoshuo Liang; Ping He; Qingnan Chu; Wentian He; Ruochen Li; Xinpeng Xu; Rong Jiang; Shuang Liu; Linkui Cao; Zhimin Sha (Field Crops Research, 2026)

11‐Year Solar Cycle Signature in the Summer Stratospheric Temperature Over the Pacific - Ruochen Wang; Liang Zhao; Haoxin Yao; Xinyong Shen; Jingsong Wang; Ziniu Xiao; Jinjuan Liu; Weiguo Zong (International Journal of Climatology, 2026)
Although previous studies have identified a quasi‐11‐year solar cycle signal in sea surface temperature and tropopause temperature over the Pacific, the existence of a solar cycle signal in the Pacific stratosphere remains underexplored. This study analyses temperature data from various levels of the Pacific stratosphere during June, July and August (JJA) from 1980 to 2022. Through regional averaging, vertical integration and power spectrum analysis, we identify a significant influence of solar activity on EOF2 of JJA‐mean 50 hPa temperature over the Pacific. This response is characterized by a meridional tripolar distribution, with cold anomalies over the equator and warm anomalies in the subtropics. Mechanism analysis shows that during high solar activity years (HSY), enhanced radiative heating in the subtropical stratosphere over the Pacific reduces the meridional temperature gradient, which weakens zonal winds according to the thermal wind principle, thus facilitating planetary wave propagation. This leads to increased wave activity, which strengthens the Brewer‐Dobson (BD) circulation. More ozone is transported from the equator to the subtropics, raising ozone concentrations, absorbing more solar ultraviolet (UV) radiation and causing warming in the subtropics. In contrast, the equatorial region experiences cooling, resulting in a meridional tripolar structure in the JJA‐mean 50 hPa temperature over the Pacific. Using the CMIP6 hist‐sol experiment, we analyse the key physical processes under the influence of solar activity and reveal how solar activity impacts ozone distribution through planetary waves and the BD circulation, ultimately affecting temperature.

The impact of green space environments on college students’ mental health at multiple spatial scales in Chinese universities: An empirical study based on a multilevel mediation model - Zhenhua Zheng; Yilin Jin; Wanting Liu; Ruochen Yin; Baitong Song; Jiajia Liu; Ning Sun; Hong Chen (Applied Geography, 2026)

An exergy-guided thermodynamic framework for the optimization of electro-membrane-based coupled process - Ruochen Shen; Yawei Du; Lurong Wang; Mengmeng Sun; Tianyi Chen; Shizhao Wang; Jingtao Bi; Wenhao Li; Jianlu Liu; Yingying Zhao (Water Research, 2026)

Intrinsic ion migration-induced susceptible two-dimensional phase-transition memristor with ultralow power consumption - Lanhao Qin; Yimeng Yu; Cheng Fang; Yujie Liu; Kaichen Zhu; Decai Ouyang; Shenghong Liu; Bailing Song; Ruochen Zhou; Mario Lanza; Wenhua Hu; Jinsong Wu; et al. (Science Bulletin, 2025)

pH/GSH-Driven inside-out nanoreactor initiating copper(I)-precursor chelation-promoted bioorthogonal therapy - Zhexiang Wang; Xinyi Li; Rui Lv; Ruochen Guo; Qinglei Shu; Tianjin Ge; Jun Yan; Zhihao Zhao; Guanghui Wang; Jian Liu (Chemical Engineering Journal, 2025)

Constrained multi-objective evolutionary algorithm based on the correlation between objectives and constraints - Jianxia Li; Ruochen Liu; Xilong Zhang; Ruinan Wang (Swarm and Evolutionary Computation, 2025)

The mechanism of human-machine collaboration driving sustainable business models: A single case study from the electric vehicle industry - Yanying Shang; Junfeng Jiang; Ruochen Zhang; Yamin Zhang; Peiqing Liu; Liqi Yu (Journal of Cleaner Production, 2025)

CRISPR/Cas-powered “sweet” DNA nano-sponge for highly sensitive detection of pathogen nucleic acid with portable personal glucometer - Huiling You; Jingwen Shan; Yang Bai; Ruochen Yang; Shulin Tan; Yueqing Gu; Baicun Li; Haiping Wu; Yunlong Liu (Chemical Engineering Journal, 2025)

Bottom-up nucleation induced conformal crystallization for inverted MA-free perovskite solar cells on textured substrates - Ruochen Liu; Jiawei Xu; Tianxiang Hu; Xiang Li; Kongxiang Wang; Qi Huang; Zhongtao Duan; Hong Liu; Weifan Qian; Haiting Zhou; Chunxiao Cong; Xiaofei Yue; et al. (Chemical Engineering Journal, 2025)

The peculiar role of iodides and formation of iodinated oligomer byproducts upon phenol mineralization with boron-doped diamond anode - Ruochen Liu; Mingjun Ouyang; Shujuan Chen; Saier Wang; Chenwei Liu; Chunyong Zhang; Hua Wu (Chemical Engineering Journal, 2024)

Saline water treatment coupled with carbon dioxide capture by bipolar membrane electrodialysis in a continuous feed-bleed mode: The effect of proton leakage - Tianyi Chen; Ruochen Shen; Hongshuo Sun; Jingtao Bi; Mengmeng Sun; Shizhao Wang; Xiaofu Guo; Wenhao Li; Jianlu Liu; Yingying Zhao (Chemical Engineering Journal, 2024)

Gasification characteristics and sulfur migration mechanism during supercritical water partial oxidation of 2-methylthiophene - Ruochen Xiong; Shi Liu; Jiayi Yu; Zhiwei Ge; Liejin Guo (Chemical Engineering Journal, 2024)

Quantitative prediction of surrounding rock deformation via an energy-based damage model combining with microseismic monitoring - Dingran Song; Yi Liu; Feng Dai; Ruochen Jiang; Ang Li (Tunnelling and Underground Space Technology, 2024)

Energy-efficient rapid additive manufacturing of complex geometry ceramics - Ruochen Liu; Aolin Hou; Prashant Dhakal; Chongjie Gao; Jingjing Qiu; Shiren Wang (Journal of Cleaner Production, 2024)

Handling dynamic capacitated vehicle routing problems based on adaptive genetic algorithm with elastic strategy - Jianxia Li; Ruochen Liu; Ruinan Wang (Swarm and Evolutionary Computation, 2024)

Global mapping of forest clumping index based on GEDI canopy height and complementary data - Xingmin Zhao; Jing M. Chen; Yongguang Zhang; Ziti Jiao; Liangyun Liu; Feng Qiu; Jinlong Zang; Ruochen Cao (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

An AI-powered approach to improving tunnel blast performance considering geological conditions - Yaosheng Liu; Ang Li; Feng Dai; Ruochen Jiang; Yi Liu; Rui Chen (Tunnelling and Underground Space Technology, 2024)

Suppression of phosphorus release and acceleration of sediment consolidation via exposure to sunlight and air (sunbathing) - Hao Hou; Wei Zhu; Jiming Liu; Xiaowei Lin; Ruochen Wang; Santao Xie; Hongyong Wu (Journal of Soils and Sediments, 2024)

Investigation into the electrochemical advanced oxidation of p-arsanilic acid: Peculiar role of electrolytes and unexpected formation of coupling byproducts - Lihua Yan; Ruochen Liu; Chunyong Zhang; Degang Fu (Science of The Total Environment, 2024)

An integrated modelling framework for multiple pollution source identification in surface water - Xiaodong Liu; Xuneng Tong; Lei Wu; Sanjeeb Mohapatra; Hongqin Xue; Ruochen Liu (Journal of Environmental Management, 2023)

Newcastle disease virus forms inclusion bodies with features of liquid-liquid phase separation - Chongyang Wang; Liuyuan Duan; Ting Wang; Wenbin Wang; Yu Han; Ruochen Hu; Qili Hou; Haijin Liu; Juan Wang; Xinglong Wang; Sa Xiao; Ruyi Dang; et al. (Veterinary Microbiology, 2023)

Multi-layer multi-objective cooperative regulation of agricultural water resources in large agricultural irrigation areas based on runoff prediction - Mo Li; Wuyuan Liu; Qiang Fu; Dong Liu; Tianxiao Li; Yaowen Xu; Ruochen Shang (Computers and Electronics in Agriculture, 2023)

Efficiency of scientific and technological resource allocation in Chengdu–Chongqing–Mianyang Urban agglomeration: based on DEA–Malmquist index model - Ruochen Li; Yuyan Luo; Borui Chen; Huan Huang; Ping Liu (Environment, Development and Sustainability, 2023)

How magnitude of PM2.5 exposure disparities have evolved across Chinese urban-rural population during 2010–2019 - Ming Liu; Yang Wang; Ruochen Liu; Chao Ding; Gaoxiang Zhou; Ling Han (Journal of Cleaner Production, 2023)

Profiling of bacterial transcriptome from ultra‐low input with MiniBac ‐seq - Tianmin Wang; Ping Shen; Ruochen Chai; Yihui He; Jintao Liu (Environmental Microbiology, 2022)
There is a lack of appropriate methods for preparing bacterial RNA‐seq library with ultra‐low amount of RNA. To address this issue, we developed miniBac‐seq, a strand‐specific method for high‐quality library construction from sub‐nanogram of total RNA, which is 100‐fold lower than the current benchmark kit and dramatically reduces preparation cost ($28 + $15 × samples). We further demonstrated the high sensitivity of miniBac‐seq via detecting more than 500 genes from amount of total RNA equivalent to that of a single bacterial cell. Finally, we profiled the transcriptome of growth‐arrested bacteria in isogenic culture of Escherichia coli . This subpopulation of bacteria is generally low in abundance but is a potent reservoir of antibiotic persistence, and their gene expression has been largely unknown due to technical limitations. Using miniBac‐seq, we identified potential molecular driver towards arrested growth as well as antibiotic tolerance. Our method thus expands the capacity to quantify bacterial transcriptome in situ, which is useful to the understanding of bacterial physiology and regulation in their native contexts.

Oceanospirillum sediminis sp. nov., Isolated From Coastal Sediment in the Yellow Sea - Huilin Zhao; Yue Tian; Xunke Sun; Qianwen Wu; Si Chen; Jiangfan Shan; Yu Zhong; Xinyu Chen; Xiaoxue Gao; Shengnan Liu; Ruochen Wang; Zongjun Du; et al. (Current Microbiology, 2022)

Seismic Performance Assessment of Velocity Pulse-Like Ground Motions Under Near-Field Earthquakes - Quanbo Luo; Feng Dai; Yi Liu; Mengtan Gao; Zongchao Li; Ruochen Jiang (Rock Mechanics and Rock Engineering, 2021)

Frequency Characteristics of Acoustic Emissions Induced by Crack Propagation in Rock Tensile Fracture - Ruochen Jiang; Feng Dai; Yi Liu; Ang Li; Peng Feng (Rock Mechanics and Rock Engineering, 2021)

Maximum July–September temperatures derived from tree‐ring densities on the western Loess Plateau, China - Huiming Song; Ruochen Mei; Yu Liu; Daniel Nievergelt; Anne Verstege; Paolo Cherubini; Ruoshi Liu; Changfeng Sun; Qiang Li; Ling Chen; Xueli Zeng; Junqin Guo (International Journal of Climatology, 2021)
Tree‐ring densitometric studies conducted in semi‐arid regions are exceedingly rare. In this study, we evaluate a new maximum latewood density chronology from a collection of Picea purpurea trees growing in semi‐arid northwestern China for climatic reconstruction purposes. We find statistically significant correlations between annual maximum density variations and July–September maximum temperatures over the 1957–2014 calibration period. Using a linear model to transfer the density variations to temperature estimates, we then reconstruct maximum summer temperatures from 1840 to 2014. Statistical analyses and verification tests demonstrate that the resulting transfer function is both reliable and stable. The reconstructed temperature series shows strong inter‐annual and decadal variability. Several extremely cool and warm years are apparent on an inter‐annual scale, while three extended cool periods and a warm period are observed on a decadal scale. In addition, the reconstructed temperature series exhibits a pattern synchronous with that of the Indian monsoon index, as well as a moderate relationship to volcanic eruptions. This densitometric study reveals typical climatic variation characteristics and provides useful data for deepening our understanding of climate history in the semi‐arid regions of China.

The phosphatidylinositol synthase gene (GhPIS) contributes to longer, stronger, and finer fibers in cotton - Qin Long; Fang Yue; Ruochen Liu; Shuiqing Song; Xianbi Li; Bo Ding; Xingying Yan; Yan Pei (Molecular Genetics and Genomics, 2018)

Tree‐ring‐based precipitation reconstruction in the source region of Weihe River, northwest China since AD 1810 - Changfeng Sun; Yu Liu; Huiming Song; Ruochen Mei; Paramate Payomrat; Lu Wang; Ruoshi Liu (International Journal of Climatology, 2018)
A tree‐ring width chronology of Picea purpurea Mast from Mt. Shouyang in the source region of Weihe River (SWR), northwest China, was developed in this study. Correlation analysis showed that the precipitation from previous August to current July was the limiting climate factor of tree growth. Using a reliable and stable linear regression model, which explained 42.6% of the variance of the actual precipitation during the calibration period from 1958 to 2014, a 205‐year long precipitation series was reconstructed for the SWR. The dry years in the reconstruction were well supported by historical documents, and famous historical droughts were also recorded in the dry periods of a low‐frequency scale of the reconstructed precipitation. As demonstrated by the spatial correlation patterns, the reconstructed series compared well with other hydroclimate records for northwest China, indicating that it could represent large‐scale hydroclimate changes. The 2–8‐year interannual cycles and the interdecadal quasiperiods of 15.9 years and 18.6 years revealed that the precipitation in this region was probably affected by the El Niño‐Southern Oscillation and North Atlantic Oscillation. The dry/wet years corresponded well with the El Niño/La Niña events and the SWR commonly experienced droughts during the low periods of North Atlantic Oscillation.

Interannual variability of PDSI from tree-ring widths for the past 278 years in Baotou, China - XinJia Zhang; Yu Liu; Huiming Song; Qiufang Cai; Qiang Li; Boyang Zhao; Han Liu; Ruochen Mei (Trees, 2017)

Tree-ring-width-based PDSI reconstruction for central Inner Mongolia, China over the past 333 years - Yu Liu; Xinjia Zhang; Huiming Song; Qiufang Cai; Qiang Li; Boyang Zhao; Han Liu; Ruochen Mei (Climate Dynamics, 2017)

Effect of silicate supplementation on the alleviation of arsenite toxicity in 93-11 (Oryza sativa L. indica) - Haichao Hu; Junting Zhang; Hong Wang; Ruochen Li; Fengshan Pan; Jian Wu; Ying Feng; Yeqing Ying; Qingpo Liu (Environmental Science and Pollution Research, 2013)